Removal of COD and Color Concentration in Batik Wastewater Using Electrofenton - Niam, Achmad Chusnun; Mirzayanti, Yustia Wulandari; Fardiansyah, Muhammad Edo; Ningsih, Erlinda (2477 - 6165, 2023)
The effluent discharged from the batik textile industry often contains azo compounds and organic contaminants. One method employed to address these pollutants is the Electrofenton (EF) technique. This study aims to assess the effectiveness of electrofenton in reducing both color content and COD (Chemical Oxygen Demand) in batik dyeing effluent. The Electrofenton process was conducted in batch mode, varying electrode distances at 4 cm and 6 cm, H2O2:FeSO4 molarity ratios of (10:0.05) and (10:0.1), and electric voltage strengths at 6 volts and 8 volts. The research revealed that employing an electric voltage of 8 volts, an electrode distance of 4 cm, a contact time of 120 minutes, and a Fenton dosage molarity of 10:0.05 M resulted in a remarkable removal efficiency of 97.8% with a final concentration of 103 mg/L for color content. Additionally, for COD, employing the same parameters led to a removal effectiveness of 90.1%, with a final concentration of 730 PtCo. The impact of Fenton dosage on COD removal was statistically analyzed using the t-test. The computed t-value of 3.444 surpassed the tabulated t-value of 2.776, indicating a significant influence of Fenton dosage on COD removal.